Fissure Seal or Fluoride Varnish? A Randomized Trial of Relative Effectiveness. (July 2017) - Chestnutt, I.G.; Playle, R.; Hutchings, S.; Morgan-Trimmer, S.; Fitzsimmons, D.; Aawar, N.; Angel, L.; Derrick, S.; Drew, C.; Hoddell, C.; Hood, K.; Humphreys, I.; et al.
Fissure sealant (FS) and fluoride varnish (FV) are effective in preventing dental caries when compared with a no-treatment control. However, the relative clinical effectiveness of these interventions is uncertain. The objective of the study was to compare the clinical effectiveness of FS and FV in preventing dental caries in first permanent molars (FPMs) in 6- to 7-y-olds. The study design was a randomized clinical trial, with 2 parallel arms. The setting was a targeted-population program that used mobile dental clinics in schools located within areas of high social and economic deprivation in South Wales. A total of 1, 016 children were randomized 1:1 to receive either FS or FV. Resin-based FS was applied to caries-free FPMs and maintained at 6-mo intervals. FV was applied at baseline and at 6-mo intervals for 3 y. The main outcome measures were the proportion of children developing caries into dentine (D4-6 MFT) on any 1 of up to 4 treated FPMs after 36 mo. At 36 mo, 835 (82%) children remained: 417 in the FS arm and 418 in the FV arm. A smaller proportion of children who received FV ( n = 73, 17.5%) versus FS ( n = 82, 19.6%) developed caries into dentine on at least 1 FPM (odds ratio [OR] = 0.84; 95% CI, 0.59 to 1.21; P = 0.35), a nonstatistically significant difference between FS and FV treatments. The results were similar when the number of newly decayed teeth (OR = 0.86; 95% CI, 0.60 to 1.22) and tooth surfaces (OR = 0.85; 95% CI, 0.59 to 1.21) were examined. In a community oral health program, semiannual application of FV resulted in caries prevention that was not significantly different from that obtained by applying and maintaining FS after 36 mo (EudraCT: 2010-023476-23; ISRCTN: ISRCTN17029222).